lncRNA and Mechanisms of Drug Resistance in Cancers of the Genitourinary System - Barth, Dominik A; Juracek, Jaroslav; Slaby, Ondrej; Pichler, Martin; Calin, George A (Cancers, 2020)
Available systemic treatment options for cancers of the genitourinary system have experienced great progress in the last decade. However, a large proportion of patients eventually develop resistance to treatment, resulting in disease progression and shorter overall survival. Biomarkers indicating the increasing resistance to cancer therapies are yet to enter clinical routine. Long non-coding RNAs (lncRNA) are non-protein coding RNA transcripts longer than 200 nucleotides that exert multiple types of regulatory functions of all known cellular processes. Increasing evidence supports the role of lncRNAs in cancer development and progression. Additionally, their involvement in the development of drug resistance across various cancer entities, including genitourinary malignancies, are starting to be discovered. Consequently, lncRNAs have been suggested as factors in novel therapeutic strategies to overcome drug resistance in cancer. In this review, the existing evidences on lncRNAs and their involvement in mechanisms of drug resistance in cancers of the genitourinary system, including renal cell carcinoma, bladder cancer, prostate cancer, and testicular cancer, will be highlighted and discussed to facilitate and encourage further research in this field. We summarize a significant number of lncRNAs with proposed pathways in drug resistance and available reported studies.
Keywords: lncRNA; drug resistance; bladder cancer; seminoma; chemoresistance; prostate cancer; renal cell carcinoma